Post Cardiotomy Extra Corporeal Membrane Oxygenation: Australian Cohort Review. - Farag, James; Summerhayes, Robyn; Shen, Rong; Bailey, Michael; Williams-Spence, Jenni; Reid, Christopher; Marasco, Silvana F (2020)
BACKGROUND: Over the last two decades, technological advancements in the delivery of extra corporeal membrane oxygenation (ECMO) have seen its use broaden and results improve. However, in the post cardiotomy ECMO patient group, survival remains very poor without significant improvements over the last two decades. Our study aims to report on the Australian experience, with the intention of providing background data for the formation of guidelines in the future. METHODS: Retrospective analysis of prospectively collected data from the Australian and New Zealand Society of Cardiothoracic Surgeons (ANZSCTS) Database was performed. The ANZSCTS database captures at least 60% of cardiac surgical data in Australia, annually. Data was collected on adult patients who received ECMO post cardiotomy from September 2016 to November 2017 inclusive. Transplant and primary cardiomyopathy patients were excluded. RESULTS: Of the 16,605 adult patients undergoing cardiac surgery in the 15-month period of the study, 87 patients required post cardiotomy ECMO (0.52%). The average age of the entire cohort was 56 years. Overall survival to discharge was 43.7% (n=38). Multivariable logistic regression analysis demonstrated that multiorgan failure (MOF), increasing age and longer cardiopulmonary bypass time were significant predictors of in hospital mortality. CONCLUSIONS: Post cardiotomy ECMO support is an uncommon condition. Survival in this study appears to be better than historical reports. Identification of poor prognostic indicators in this study may help inform the development of guidelines for the most appropriate use of this support modality.